Nitrofurantoin‑induced liver injury: long‑term follow‑up in two prospective DILI registries - Bessone, Fernando; Ferrari, Antonella; Hernandez, Nelia; Mendizabal, Manuel; Zerega, Alina; Tanno, Federico; Reggiardo, Maria Virginia; Vorobioff, Julio; Tanno, Hugo; Arrese, Marco; Nunes, Vinicius; Tagle, Martin; et al. (Springer Nature, 2022)
Nitrofurantoin is a synthetic antibiotic that is recommended as first-choice treatment for uncomplicated urinary tract infections. The prescription of this drug has increased dramatically, especially in Latin American countries. We described the demographics, clinical characteristics, biochemical features, and outcome of nitrofurantoin-induced liver injury. We analyzed 23 cases from the Latin American DILI Network (LATINDILI) and the Spanish DILI Registry. Causality was assessed with the RUCAM and RECAM scale. Of the 23 DILI cases included in our series, 96% patients were women, and the mean age of the whole cohort was 61 years. The median time of drug exposure was 175 days (interquartile range [IQR] 96–760), with 11 patients who were prescribed nitrofurantoin for more than six months. Hepatocellular damage was the most frequent pattern of liver injury (83%), and nearly half of the patients had an asymptomatic presentation (52%). Neither death nor liver transplantation was documented in this series. Overall, 65% of the patients (n = 15) presented with positive autoantibody titres. The median time to resolution was 81 days (IQR 57–141), and 15 patients (83%) recovered within six months. Five patients (22%) developed nitrofurantoin-induced autoimmune-like hepatitis (NI-AILH), of whom two were characterized by a persistent increase in transaminases that required immunosuppressive treatment to achieve normalization of liver enzymes. Clinicians who prescribe nitrofurantoin should be aware that patients who had taken nitrofurantoin for a long term may be at risk of developing nitrofurantoin-induced autoimmune-like hepatitis.
Keywords: Toxicología; Hepatitis; Antibióticos -- Efectos secundarios; Hepatotoxicity; Autoimmune-like hepatitis; Nitrofurantoin; Drug-induced liver injury